2003
DOI: 10.1159/000069122
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Recurrent Spontaneous Miscarriage with Reproductive Failure

Abstract: Objective: To investigate the reproductive performance of non-pregnant women with recurrent spontaneous miscarriage (RSM) and the association between RSM and polycystic ovary syndrome (PCOS) in reproductive failure. Subjects and Methods: Fifty non-pregnant women with 3 or more consecutive RSM attending our RSM clinic were evaluated prospectively. Detailed history and physical examination were completed. Extensive laboratory investigations, ultrasonographic, radiological and specialized procedures/tests were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) has been associated with an increased risk of miscarriage and RSM, although the exact mechanism for this association remains uncertain [5,47] and the incidence reported is quite varied: PCOS has been associated with RSM in 56% of the population [62,63], whereas a rate of 21.1-40% was reported from Kuwait [64,65] and a lower rate of 8.3-10% in the study of Cocksedge et al [66]. Hyperinsulinaemia, increased insulin resistance and hyperandrogenaemia, which have all been reported in PCOS, have been linked with an increased risk of miscarriage and RSM.…”
Section: The Aetiology Of Rsmmentioning
confidence: 99%
See 3 more Smart Citations
“…Polycystic ovary syndrome (PCOS) has been associated with an increased risk of miscarriage and RSM, although the exact mechanism for this association remains uncertain [5,47] and the incidence reported is quite varied: PCOS has been associated with RSM in 56% of the population [62,63], whereas a rate of 21.1-40% was reported from Kuwait [64,65] and a lower rate of 8.3-10% in the study of Cocksedge et al [66]. Hyperinsulinaemia, increased insulin resistance and hyperandrogenaemia, which have all been reported in PCOS, have been linked with an increased risk of miscarriage and RSM.…”
Section: The Aetiology Of Rsmmentioning
confidence: 99%
“…In 50-60% of patients, the aetiology of RSM remains elusive, unidentified or unexplained [65,70]. An immunological reason has been proposed as the underlying basis of these unexplained RSM [71] although the exact mechanism has not been elucidated.…”
Section: The Aetiology Of Rsmmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a combination of clinical, ultrasonographic, and biochemical criteria, the diagnosis of PCOS is usually reserved for those women who display one or more clinical symptoms including chronic anovulation, an ultrasonographical morphology of polycystic ovaries, inappropriate gonadotropin secretion, and hyperandrogenism (Franks, 1995;Dunaif, 1997). It is reported that women with PCOS have adverse pregnancy outcome including miscarriage (Abbott et al, 2002;Doldi et al, 1998;Glueck et al, 1999;Wang et al, 2001;Diejomaoh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%